1994
DOI: 10.1161/01.cir.89.3.1247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of atherosclerosis by dietary pectin in microswine with sustained hypercholesterolemia.

Abstract: Sustained hypercholesterolemia is a known risk factor for development of atherosclerosis. In animal studies, grapefruit pectin fed concurrently with a high-lipid diet inhibits hypercholesterolemia and atherogenesis. The purpose of the present study was to determine if grapefruit pectin affects cholesterol levels and atherogenesis of animals with established hypercholesterolemia. Microswine were fed an atherogenic diet to establish hypercholesterolemia. Plasma cholesterol levels rose rapidly and for 360 days we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…09, 26.01, 32,45 and 30.78% for raw and steamed broccoli and cauliflower respectively, compared to the basal diet. These results are in agreement with the findings of Cerda et al (1994) and Jenkins et al (1997), whereas they reported that the lipid risk factor for cardiovascular diseases for healthy volunteers were significantly reduced after 2 weeks of feeding on high vegetable diets including broccoli and cauliflower, in comparison with control diet. They also found that LDL was reduced by 37% for those fed in high vegetable diets.…”
Section: Effect Of Raw and Steamed Broccoli And Cauliflower Diets On supporting
confidence: 91%
“…09, 26.01, 32,45 and 30.78% for raw and steamed broccoli and cauliflower respectively, compared to the basal diet. These results are in agreement with the findings of Cerda et al (1994) and Jenkins et al (1997), whereas they reported that the lipid risk factor for cardiovascular diseases for healthy volunteers were significantly reduced after 2 weeks of feeding on high vegetable diets including broccoli and cauliflower, in comparison with control diet. They also found that LDL was reduced by 37% for those fed in high vegetable diets.…”
Section: Effect Of Raw and Steamed Broccoli And Cauliflower Diets On supporting
confidence: 91%
“…However, the wide consumption of grapefruit juice cannot entirely be attributed to its taste, and nutritive value. In fact, much of the enthusiasm in its use stems from medical research that has suggested that grapefruit juice reduces atherosclerotic plaque formation [ 2 ] and inhibits breast cancer cell proliferation and mammary cell tumorigenesis [ 3 , 4 ]. Traditionally grapefruit juice has been found to contain antioxidant, antinitrosaminic, antiseptic, aperitif, cardiotonic, detoxicant, hypocholesterolemic, sedative and stomachic activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, pectin supplementation (3% wt=wt) in swine reduced mean surface area lesion development from 13.6% to 5.3% and reduced coronary artery narrowing from 45% to 24% despite no observable change in serum cholesterol. 15 Additionally, proanthocyanidin-rich grape seed extract reduced histologic markers of atherosclerosis with no noticeable change in serum lipids. 20,21 Hence longer-term studies with nutritional supplements should also evaluate the prevention of atherosclerosis by quantitation of gross pathological changes in FH swine, which spontaneously develop advanced atherosclerotic lesions and coronary artery disease with myocardial infarction and ischemia similar to humans.…”
Section: Discussionmentioning
confidence: 99%